Um exame da recepção da bossa nova pela crítica jornalística: renovação na música popular sob o olhar da crítica - Bollos, Liliana Harb (2007)
The principal objective of this research is to discuss the critical reception of the first phenomena of popular Brazilian music and the interest of the press at large in the Bossa Nova. It attempts also to insert literary criticism into the formation of modern Brazilian criticism, therefore including journalistic criticism, capable of creating parameters for other art critics. The body of the work consists of critiques made available by the researcher, José Ramos Tinhorão, through the Moreira Salles Institute in Sao Paulo. Added to these are collections from the popular music magazine, Revista Clima, and in additional books, the important example of the literary supplement of the newspaper, O Estado de São Paulo. (The State of Sao Paulo). The methodology involved a lengthly and exhaustive study of the pioneering critics of Bossa Nova. The theoretic body of the study deals with a group of works on the ideas of Mario de Andrade and the thinking borne from him, the example of the Clima Group incontradiction with the universalist vision of Oswald de Andrade, and reexaminations by the concrete poets and by Caetano Veloso. As a result, it is argued that the reception of the Bossa Nova in the press was a polyphony of voices in dialogue, in spite of the various dissonant chords that may have existed among them. The formation of two distinct groups of critics is perceived, two schools of thought, one sociologic and one esthetic, represented fy two books of criticism in the 1950s: Popular music in Debate (J.R.Tinhorão) and the Swing of Bossa (Augusto de Campos)